Continued changes to contact lens practice following adjustments made as a result of the COVID-19 pandemic - Federica Scarci; Alfredo Desiato; Giulia Carlotta Rizzo; Stefano Livi; Mara Marini; Alessandra Cecalupo; Silvia Tavazzi; Shehzad A. Naroo; Fabrizio Zeri (Heliyon)
Background: This study aimed to explore behaviour of practitioners in response to the COVID-19 pandemic, analysing the factors that influenced their decisions to resume professional practice post-lockdown and intention to adhere to COVID-19 protective measures. Methods: A web-based cross-sectional survey targeting Italian practitioners was carried out to study the post lockdown behaviour and future intention to provide new contact lens (CL) fittings, and the use of protective measures. The survey also explored the dimensions of the Integrated Behavioural Model (IBM) and the Health Belief Model (HBM) to predict the intention to resume professional practice and to comply with protective measures respectively. Results: A total of 212 professional (150 males; age range 22–76 years) completed the survey. Past behaviour and positive attitudes toward CL practice were the variable in IBM that predicted more strongly the intention to provide both new CL fittings and aftercare visits, whereas past behaviour and perceived benefits of HBM were the strongest predictors of future compliance with protective measures. Conclusion: Results suggest that the more engaged practitioners are more willing to get back to their routine even in uncertain circumstances, and that a tailored approach, leveraging past behaviours and perceived benefits, could enhance compliance strategies.